Fostering Outstanding Personality among Teacher Trainees through ULUL Albab QEI Module Training (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Purpose – This study centres on a new cohort of teacher training students in Universiti Pendidikan Sultan Idris (UPSI) who were trained on the attitude and personality development modules organised by the Ulul Albab Centre in the university. The Ulul Albab modules known as QEI (Quranic, Encyclopaedic and Ijtihadik) were introduced and conducted with the participants of Ulul Albab Centre (PUA) programme. The QEI modules cover leadership talent development and soft skills which are considered as the important characteristics of outstanding personality for every future educators and community leaders. A standard questionnaire was distributed to 150 students who were pioneers of the Ulul Albab programme in the university. The participants were also asked to reflect on the various aspects and activities of the programme and modules and their written and verbal responses were analysed using NVivo 12 application. The findings indicated more than 80% approval and satisfaction rate among the participants on the constructive impact of the training on their attitude, personal and soft skills development. Their feedback and personal reflections too indicated positive bearing on their overall attitude having completed all the Ulul Albab modules. The encouraging outcomes are signs of better programme implementation for the new batch of teacher trainees. New ideas and suggestions from the participants’ feedback would be integrated for the improvement of the QEI components for future cohorts and stronger plans ahead for Pusat Ulul Albab UPSI.